A hydroxyl-mediated TiO2@Al-based porphyrin MOFs composite photocatalyst, its preparation method and application

CN122875293APending Publication Date: 2026-10-09YANCHENG INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611034862.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-13
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

但传统复合方式多为简单物理复合,存在界面结合松散、相容性差等问题,严重抑制界面电荷快速迁移分离,无法充分利用MOFs酸性位点的定向催化优势,大幅限制了光催化产H2O2效率

Benefits of technology

[0015]与现有技术相比,本发明提供了一种羟基介导的TiO2@Al基卟啉MOFs复合光催化剂及其制备方法和应用,具有以下有益效果:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122875293A_ABST
    Figure CN122875293A_ABST
Patent Text Reader

Abstract

The application discloses a kind of hydroxyl-mediated TiO2@Al base porphyrin MOFs composite photocatalyst and its preparation method and application.The method is carried out surface hydroxyl modification to TiO2 Nanofiber using hydrogen peroxide-ammonia mixed system, constructs high-density Ti-OH covalent anchoring site;Again, in situ coordination coating growth method, in situ constructs continuous Al base porphyrin MOFs coating layer on the surface of hydroxylated fiber.The obtained TiO2@Al base porphyrin MOFs binary composite photocatalyst can efficiently prepare H2O2 in pure water without sacrificial agent system, and has significant application potential in production.The innovation of the application is that TiO2 surface hydroxyl can be used as a hole capture site, and can continuously supply protons for oxygen reduction reaction, combined with the Lewis acid site of Al base porphyrin MOFs to direct control oxygen double-electron reduction path, the effective survival time of two-phase covalent connection heterojunction interface is extended, combined with the continuous supply of protons by hydroxyl, direct push oxygen double-electron reduction, greatly improve the efficiency of hydrogen peroxide production.The whole process does not use noble metal raw materials, raw materials are easy to get, easy to operate, suitable for green liquid phase hydrogen peroxide low-cost continuous preparation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of photocatalyst technology, specifically relating to a hydroxyl-mediated TiO2@Al-based porphyrin MOFs composite photocatalyst, its preparation method, and its application. Background Technology

[0002] Hydrogen peroxide (H2O2) is a core green oxidant in environmental remediation and fine chemical industries. Compared to the traditional high-energy-consuming and high-polluting anthraquinone preparation process, photocatalytic oxygen two-electron reduction to H2O2 has become a research hotspot for novel green synthesis technologies due to its mild conditions and lack of pollution. Single TiO2 only responds to ultraviolet light and has a high recombination rate of photogenerated carriers, making the oxygen reduction pathway uncontrollable and limiting its H2O2 production performance. Al-based porphyrin MOFs possess excellent visible light response, porous structure, and abundant Lewis acidic active sites, allowing for precise control of the reduction pathway, making them ideal functional materials for modifying TiO2. Constructing a covalent heterojunction between the two can complement each other's performance shortcomings and fully leverage their synergistic catalytic advantages. However, traditional composite methods are mostly simple physical composites, suffering from loose interfacial bonding and poor compatibility, severely inhibiting the rapid migration and separation of interfacial charges, failing to fully utilize the directional catalytic advantages of MOFs' acidic sites, and significantly limiting the efficiency of photocatalytic H2O2 production.

[0003] To address the aforementioned technical shortcomings, this invention abandons traditional physical composite methods and modifies TiO2 nanofibers with hydrogen peroxide-ammonia hydroxylation. Utilizing the covalent coordination between hydroxyl groups on the substrate surface and Al metal centers, a robust TiO2@Al-based porphyrin MOF binary heterostructure is constructed through an in-situ coordination coating growth method. The hydroxylated TiO2 constructs hole-trapping sites and provides a proton source for the reaction. Combined with the Lewis acidic sites of the Al-based porphyrin MOFs, it directionally induces a two-electron reduction pathway for oxygen. Accelerating charge separation through a stable heterojunction interface effectively solves the problems of interfacial defects and low catalytic efficiency in traditional composite materials, achieving efficient and stable photocatalytic green synthesis of H2O2. This provides a novel approach for low-cost, metal-free photocatalytic synthesis of hydrogen peroxide, possessing significant theoretical research value and practical application significance for overcoming the bottlenecks of existing photocatalytic hydrogen peroxide production technologies and promoting the industrialization and application of green chemical conversion technologies. Summary of the Invention

[0004] To address the problems of existing technologies, this invention provides a hydroxyl-mediated TiO2@Al-based porphyrin MOFs composite photocatalyst, its preparation method, and its application.

[0005] The technical solution adopted in this invention is: a hydroxyl-mediated TiO2@Al-based porphyrin MOFs composite catalyst, the preparation method of which includes the following steps:

[0006] Step 1: Highly crystalline TiO2 nanofibers are obtained by electrospinning a TiO2 precursor solution containing tetraisopropyl titanate (TIP), polyvinylpyrrolidone (PVP), acetic acid and ethanol, followed by high-temperature calcination.

[0007] Step 2: Immerse the TiO2 fiber membrane in a mixed modified solution of hydrogen peroxide-ammonia-water, and after thorough immersion at room temperature, filter and wash to obtain TiO2 nanofibers with a surface rich in Ti-OH.

[0008] Step 3: Prepare Al-based porphyrin MOF coating layer using in-situ coordination coating growth method; place hydroxyl-modified TiO2 fibers sequentially in aluminum chloride DMF solution and tetrakis(4-carboxyphenyl)porphyrin (C 48 H 30 By cyclically immersing the TiO2@Al-based porphyrin MOFs in a DMF solution for 10-20 cycles, a complete coating layer can be continuously grown in situ on the fiber surface by relying on the covalent induction of Ti-OH on the surface, thus obtaining a hydroxyl-mediated TiO2@Al-based porphyrin MOFs composite photocatalyst.

[0009] In the above-mentioned hydroxyl-mediated TiO2@Al-based porphyrin MOFs composite catalyst, in step 1, the precursor solution consists of 2.5-4 g tetraisopropyl titanate, 0.35-0.5 g polyvinylpyrrolidone, 4-6 mL acetic acid, and 4-6 mL ethanol. The muffle furnace temperature is 550-700 ℃, and the time is 3-5 h.

[0010] In the above-mentioned hydroxyl-mediated TiO2@Al-based porphyrin MOFs composite catalyst, in step 2, the volume ratio of hydrogen peroxide, ammonia, and water is 2:1:5, and the soaking time is 2-12 h.

[0011] In the aforementioned hydroxyl-mediated TiO2@Al-based porphyrin MOFs composite catalyst, step 3 involves an aluminum chloride DMF solution concentration of 25-35 mM, a heating temperature of 110-130 °C, a heating time of 2-3 h, and an organic ligand of tetrakis(4-carboxyphenyl)porphyrin (C 48 H 30 The solution is a DMF solution with a concentration of 3-5 mM (N4O8).

[0012] The above-mentioned hydroxyl-mediated TiO2@Al-based porphyrin MOFs composite catalyst is used in the photocatalytic production of H2O2.

[0013] In the above application, the method is as follows: 10 mg of catalyst is dispersed in 50 mL of deionized water in a sealed quartz apparatus equipped with a cooling circulation system; then, a flow rate of 20 mL / min is introduced. -1N2 gas was introduced and a 300 W xenon lamp was started for continuous reaction for 1.5 h. Every 30 min, 3 mL of sample was taken from the reactor, and the catalyst in each sample was filtered out using a disposable 0.22 μm aqueous filter. A pre-prepared colorimetric reagent was added, and the absorbance was measured using a spectrophotometer. The corresponding concentration was obtained by substituting the absorbance into a standard curve.

[0014] Beneficial effects:

[0015] Compared with the prior art, the present invention provides a hydroxyl-mediated TiO2@Al-based porphyrin MOFs composite photocatalyst, its preparation method and application, which has the following beneficial effects:

[0016] 1. The protons donated by the hydroxyl groups on the TiO2 surface and the Lewis acidic sites of Al-based porphyrin MOFs induce the oxygen two-electron reduction pathway reaction, avoiding the four-electron complete reduction side reaction and significantly improving the H2O2 production yield.

[0017] 2. A large number of Ti-OH active sites form stable covalent bonds with the Al metal center. The tight covalent heterojunction interface between the two phases prolongs the effective lifespan of photogenerated carriers. Combined with the continuous proton supply by hydroxyl groups, it directionally promotes the two-electron reduction of oxygen. Attached Figure Description

[0018] Figure 1 This is a schematic diagram illustrating the design, synthesis, and application of the present invention.

[0019] Figure 2 The image shows the XRD pattern of the TiO2@Al-based porphyrin MOFs material in Example 1 of this invention.

[0020] Figure 3 This is a scanning electron microscope image of the TiO2@Al-based porphyrin MOFs material in Example 1 of the present invention.

[0021] Figure 4 XPS spectrum analysis of TiO2@Al-based porphyrin MOFs material in Example 1 of this invention: a) is the 1s energy spectrum of C, b) is the 1s energy spectrum of O, c) is the 2p energy spectrum of Ti, and d) is the 2p energy spectrum of Al.

[0022] Figure 5 The absorbance of the ultraviolet spectrophotometer in Example 1 of this invention corresponds to different hydrogen peroxide standard solutions.

[0023] Figure 6 This is the standard curve of hydrogen peroxide in Example 1 of the present invention.

[0024] Figure 7 This is a comparison chart showing the efficiency of TiO2@Al-based porphyrin MOFs materials in the photocatalytic synthesis of hydrogen peroxide in Example 1 of this invention.

[0025] Figure 8 This demonstrates the reproducibility of the photocatalytic synthesis of hydrogen peroxide using TiO2@Al-based porphyrin MOFs materials in Example 1 of this invention. Detailed Implementation

[0026] To better understand the technical solution of the present invention, specific embodiments are provided for further detailed description, but the solution is not limited thereto.

[0027] Example 1: A hydroxyl-mediated TiO2@Al-based porphyrin MOFs composite photocatalyst

[0028] The preparation method is as follows:

[0029] Step 1: Highly crystalline TiO2 nanofibers were obtained by electrospinning a TiO2 precursor solution containing 2.5 g tetraisopropyl titanate (TIP), 0.35 g polyvinylpyrrolidone (PVP), 4 mL acetic acid and 6 mL ethanol, followed by high-temperature calcination at 550℃ for 3 h.

[0030] Step 2: Immerse the TiO2 fiber membrane in a mixed modified solution of hydrogen peroxide-ammonia-water (2:1:5) for 6 h. After thorough immersion at room temperature, filter and wash to obtain TiO2 nanofibers with Ti-OH hydroxyl functionalization on the surface.

[0031] Step 3: Prepare Al-based porphyrin MOF coating layer using in-situ coordination coating growth method; place hydroxyl-modified TiO2 fibers sequentially in aluminum chloride DMF solution (concentration 25 mM) and tetrakis(4-carboxyphenyl)porphyrin (C 48 H 30 By immersing the TiO2@Al-based porphyrin MOFs in a DMF solution (3 mM N4O8) at 110 °C for 2 h for a total of 15 times, a complete coating layer of Al-based porphyrin MOFs was continuously grown in situ on the fiber surface by covalent induction of Ti-OH on the surface, thus obtaining a hydroxyl-mediated TiO2@Al-based porphyrin MOFs composite photocatalyst.

[0032] Example 2: A hydroxyl-mediated TiO2@Al-based porphyrin MOFs composite photocatalyst

[0033] The preparation method is as follows:

[0034] Step 1: Highly crystalline TiO2 nanofibers were obtained by electrospinning a TiO2 precursor solution containing 3.5 g tetraisopropyl titanate (TIP), 0.45 g polyvinylpyrrolidone (PVP), 5 mL acetic acid and 5 mL ethanol, followed by calcination at 650℃ for 4 h.

[0035] Step 2: Immerse the TiO2 fiber membrane in a mixed modified solution of hydrogen peroxide-ammonia-water (2:1:5) for 2 h. After thorough immersion at room temperature, filter and wash to obtain TiO2 nanofibers with Ti-OH hydroxyl functionalization on the surface.

[0036] Step 3: Prepare Al-based porphyrin MOF coating layer using in-situ coordination coating growth method; place hydroxyl-modified TiO2 fibers sequentially in aluminum chloride DMF solution (concentration 30 mM) and tetrakis(4-carboxyphenyl)porphyrin (C 48 H 30 The TiO2@Al-based porphyrin MOFs composite photocatalyst was obtained by immersing the product in a DMF solution (4 mM N4O8) at 120 °C for 2.5 h for a total of 10 cycles. The complete coating layer of Al-based porphyrin MOFs was continuously grown in situ on the fiber surface by relying on the covalent induction of Ti-OH on the surface.

[0037] Example 3: A hydroxyl-mediated TiO2@Al-based porphyrin MOFs composite photocatalyst

[0038] The preparation method is as follows:

[0039] Step 1: Highly crystalline TiO2 nanofibers were obtained by electrospinning a TiO2 precursor solution containing 4 g tetraisopropyl titanate (TIP), 0.6 g polyvinylpyrrolidone (PVP), 6 mL acetic acid and 4 mL ethanol, followed by high-temperature calcination at 700 °C for 5 h.

[0040] Step 2: Immerse the TiO2 fiber membrane in a mixed modified solution of hydrogen peroxide-ammonia-water (2:1:5) for 12 h. After immersion at room temperature, filter and wash to obtain TiO2 nanofibers with Ti-OH hydroxyl functionalization on the surface.

[0041] Step 3: Prepare Al-based porphyrin MOF coating layer using in-situ coordination coating growth method; place hydroxyl-modified TiO2 fibers sequentially in aluminum chloride DMF solution (concentration 35 mM) and tetrakis(4-carboxyphenyl)porphyrin (C 48 H 30 By immersing the TiO2@Al-based porphyrin MOFs in a DMF solution (5 mM N4O8) at 130 °C for 3 h for a total of 20 times, a complete coating layer of Al-based porphyrin MOFs was continuously grown in situ on the fiber surface by covalent induction of Ti-OH on the surface, thus obtaining a hydroxyl-mediated TiO2@Al-based porphyrin MOFs composite photocatalyst.

[0042] The hydroxyl-mediated TiO2@Al-based porphyrin MOFs composite photocatalyst synthesized in Example 1 was subjected to XRD powder diffraction, scanning electron microscopy, XPS analysis, H2O2 standard curve construction, and photocatalytic synthesis of H2O2. The results are as follows:

[0043] A schematic diagram illustrating the design, synthesis, and application of the hydroxyl-mediated TiO2@Al-based porphyrin MOFs composite photocatalyst of this invention is shown below. Figure 1 As shown.

[0044] Figure 2 For the comparison of the XRD patterns of the samples, the test results show that the hydroxyl-mediated TiO2@Al-based porphyrin MOFs composite photocatalyst exhibits typical diffraction patterns of both Al-based porphyrin MOFs and TiO2, indicating the successful preparation of the composite material.

[0045] Figure 3 Scanning electron microscopy images show that Al-based porphyrin MOF crystals are tightly coated on the surface of TiO2 nanofibers, confirming that the binary covalently coated film grows uniformly without obvious interface defects.

[0046] Figure 4 The XPS spectra shown indicate that the high-resolution C 1s spectrum can be divided into two peaks, located at 284.8 eV and 288.5 eV, which can be attributed to the C-C and OC=O bonds of the ligands in the Al-based porphyrin MOFs framework. The two peaks at 529.8 eV and 531.7 eV in the O 1s spectrum correspond to O−C=O and C−O, respectively. The Ti 2p of TiO2@Al-based porphyrin MOFs... 3 / 2 and Ti2p 1 / 2 The binding energies are located at 458.8 eV and 464.4 eV, respectively. TiO2@Al-based porphyrin MOFs exhibit a characteristic peak at 74.65 eV, indicating successful loading of Al-based porphyrin MOFs.

[0047] The results of constructing the H2O2 standard curve are as follows:

[0048] like Figure 5 As shown, under acidic conditions, H2O2 oxidizes I⁻ in potassium iodide to I₂ using ammonium molybdate as a catalyst. I₂ then reacts with excess I⁻. - Combine to form I3 - It has a characteristic absorption at 350 nm.

[0049] like Figure 6 As shown, the absorbance has a linear relationship with the concentration of H2O2.

[0050] The test results of the photocatalytic H2O2 reduction performance are as follows:

[0051] like Figure 7As shown, the photocatalytic activity of the material is significantly enhanced after the formation of the composite structure. The photocatalytic performance of the TiO2@Al-based porphyrin MOFs composite is far superior to that of the single component. Single TiO2 nanofibers and Al-based porphyrin MOFs exhibit extremely low photocatalytic efficiency, with only a small amount of H2O2 detected. The H2O2 yield of TiO2@Al-based porphyrin MOFs is 736.94 μmol g. -1 h -1 The product synthesis rate of TiO2@Al-based porphyrin MOFs was 12.79 times that of TiO2 and 3.34 times that of Al-based porphyrin MOFs, respectively. Compared with the single-component system, the product synthesis rate of TiO2@Al-based porphyrin MOFs composites was higher.

[0052] Figure 8 Repeatability studies showed that the prepared hydroxyl-mediated TiO2@Al-based porphyrin MOFs composite photocatalyst exhibited good cycling stability in a pure water reaction system.

[0053] The embodiments described above are some, but not all, embodiments of the present invention. The detailed description of the embodiments of the present invention is not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.

Claims

1. A hydroxyl-mediated TiO2@Al-based porphyrin MOFs composite photocatalyst, its preparation method, and its application, characterized in that, Its preparation method includes the following steps: Step 1: Highly crystalline TiO2 nanofibers are obtained by electrospinning a TiO2 precursor solution containing tetraisopropyl titanate (TIP), polyvinylpyrrolidone (PVP), acetic acid and ethanol, followed by high-temperature calcination. Step 2: Immerse the TiO2 fiber membrane in a mixed modified solution of hydrogen peroxide-ammonia-water, and after thorough immersion at room temperature, filter and wash to obtain TiO2 nanofibers with a surface rich in Ti-OH. Step 3: Prepare Al-based porphyrin MOF coating layer using in-situ coordination coating growth method; place hydroxyl-modified TiO2 fibers sequentially in aluminum chloride DMF solution and tetrakis(4-carboxyphenyl)porphyrin (C 48 H 30 By cyclically immersing the TiO2@Al-based porphyrin MOFs in a DMF solution for 10-20 cycles, a complete coating layer can be continuously grown in situ on the fiber surface by relying on the covalent induction of Ti-OH on the surface, thus obtaining a hydroxyl-mediated TiO2@Al-based porphyrin MOFs composite photocatalyst.

2. The hydroxyl-mediated TiO2@Al-based porphyrin MOFs catalyst and its preparation method according to claim 1, characterized in that, In step 1, the precursor solution consists of 2.5-4 g tetraisopropyl titanate, 0.35-0.5 g polyvinylpyrrolidone, 4-6 mL acetic acid, and 4-6 mL ethanol. The muffle furnace temperature is 550-700 ℃, and the time is 3-5 h.

3. The hydroxyl-mediated TiO2@Al-based porphyrin MOFs catalyst and its preparation method according to claim 1, characterized in that, In step 2, the volume ratio of hydrogen peroxide, ammonia, and water is 2:1:5, and the soaking time is 2-12 hours.

4. The hydroxyl-mediated TiO2@Al-based porphyrin MOFs catalyst and its preparation method according to claim 1, characterized in that, In step 3, the concentration of the aluminum chloride DMF solution is 25-35 mM, the heating temperature is 110-130 ℃, the heating time is 2-3 h, and the organic ligand is tetrakis(4-carboxyphenyl)porphyrin (C 48 H 30 The solution is a DMF solution with a concentration of 3-5 mM (N4O8).

5. The application of the hydroxyl-mediated TiO2@Al-based porphyrin MOFs composite photocatalyst according to claim 1 in the photocatalytic production of H2O2, characterized in that: In a sealed quartz apparatus equipped with a cooling circulation system, 10 mg of catalyst was dispersed in 50 mL of deionized water; then, a flow rate of 20 mL / min was introduced. -1 The reactor was filled with N2 gas and a 300 W xenon lamp was started, and the reaction was carried out continuously for 1.5 h. Every 30 min, 3 mL of sample was taken from the reactor, and the catalyst in each sample was filtered out using a disposable 0.22 μm aqueous filter. A pre-prepared colorimetric reagent was added, and the absorbance was measured using a spectrophotometer. Substitute the values ​​into the standard curve to obtain the corresponding concentration.